2014
DOI: 10.2965/jwet.2014.231
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nutrient Export Coefficients in Lake Victoria Basin

Abstract: Lake Victoria in East Africa is the second largest freshwater lake in the world by surface area. Pollution of the lake is an increasing concern because it compromises the ecosystem integrity of the lake. Past studies estimated the runoff load using borrowed nutrient export coefficients from other regions. Borrowed export coefficients were not necessarily modified to match the attributes of the local area. This study estimated the nutrient export coefficients for three land uses using river runoff data measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The unique shape of the lake has some of its parts protruding inland such as Winam Gulf on the Kenyan side of Lake Victoria. The gulf is long, slender, shallow, semi-enclosed and bottlenecked at the point of connection to the main lake (Cheruiyot and Muhandiki, 2014a). It has a surface area of 1,400 km 2 , an average depth of 10 m (Calamari et al, 1995) and connects to the main lake at Rusinga channel ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The unique shape of the lake has some of its parts protruding inland such as Winam Gulf on the Kenyan side of Lake Victoria. The gulf is long, slender, shallow, semi-enclosed and bottlenecked at the point of connection to the main lake (Cheruiyot and Muhandiki, 2014a). It has a surface area of 1,400 km 2 , an average depth of 10 m (Calamari et al, 1995) and connects to the main lake at Rusinga channel ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical parameters, including land use coefficients, urban domestic household coefficients, and industrial wastewater coefficients, were adopted in this study. We adopted parameters from Frontiers in Environmental Science frontiersin.org areas with similar spatial backgrounds to the study area by drawing on the practices of other scholars from different times (Calamari et al, 1995;van Horen, 1996;Young et al, 1996;Scheren et al, 2000;Jonsson et al, 2004;Abira et al, 2005;Awiti, 2006;Cheruiyot and Muhandiki, 2014;Xiong et al, 2020).…”
Section: Data Source and Processingmentioning
confidence: 99%
“…The nitrogen export coefficient of land use in the Lake Victoria Basin over different periods (Supplementary Annex Table S1) shows that nitrogen export in cropland is generally higher than that of forest and grassland, while nitrogen export in constructed land is close to or higher than cropland (Calamari et al, 1995;Van Horen, 1996;Scheren et al, 2000;Awiti, 2006). However, Cheruiyot and Muhandiki (2014) reported that the nitrogen output of forest and grassland in Kenya is much higher than that of cropland, suggesting land use differences in different geographies can lead to variation in nitrogen pollution in Africa. The export coefficients of different land use types in the eastern Australian river basin (Young et al, 1996) in the southern hemisphere showed annual average rainfalls close to our study area, suggesting that the nitrogen emission in forests is the lowest among all land use types.…”
Section: Data Source and Processingmentioning
confidence: 99%
“…Freshwater ecosystems are a powerhouse of biodiversity, currently threatened by environmental perturbations associated with human-induced activities [1][2][3][4][5][6][7]. Te disturbances in freshwater ecosystems alter natural biogeophysical processes through increased eutrophication, acidifcation, and input of toxic pollutants [8][9][10][11]. Lake Victoria ecosystem is no exception [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%